The Level of N-Carboxymethyllysine and C-Reactive Protein in Type 2 Diabetes Mellitus and it’s Association with HbA1c in Diabetic Nephropathy - Mat Rahim, Mohd Zulhafiz; Wan Azman, Wan Norlina; Yaacob, Najib Majdi; Wan Mohamed, Wan Mohd Izani; Shafii, Noorazliyana (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: N-Carboxymethyllysine (CML) is involved in diabetic nephropathy (DN) via production of oxidative stress, growth factors and cytokines. C-reactive protein (CRP) is an inflammatory marker associated with diabetes risk. This study is to determine the level of serum CML and CRP in Type 2 diabetes mellitus (T2DM) patients and healthy subjects and to determine the correlation between CML and CRP with glycated haemoglobin (HbA1c) in T2DM patients. Methods: This is a case-control study on 73 T2DM patients without nephropathy, 74 T2DM patients with nephropathy and 73 healthy subjects, aged from 18 to 65 years old. Fasting venous blood was taken and ana- lysed for CML, CRP, HbA1c, and creatinine. The comparisons of serum CML and CRP among the three groups and the correlation between CML and CRP with HbA1c (in T2DM patients) were determined. Results: The differences in CML [median (Interquartile Range) (IQR)] between healthy subjects [131.80 (73.56) ng/ml] and T2DM patients with- out nephropathy [188.80 (55.95) ng/ml]; between healthy subjects and T2DM patients with nephropathy [237.70 (439.04) ng/ml] were statistically significant (P<0.001). The differences in CRP [median (IQR)] between healthy subjects [1.64 (1.91) ng/ml] and T2DM patients without nephropathy [2.15 (5.64) ng/ml]; between healthy subjects and T2DM patients with nephropathy [4.75 (6.91) ng/ml] were statistically significant (P<0.001). Logistic regression showed CML and CRP are independent predictors of diabetic groups. There was no correlation between HbA1c with CML and CRP in T2DM groups. Conclusion: Since serum CML and CRP are independent predictors of DN, their levels can be used to identify high-risk diabetic patients prone to developing DN.